The relationship between smoking and exercise among physical education teachers in Turkey. - Gundogdu, Cemal; Oguzoncul, A Ferdane (My University, 2013)
We studied the relationship between smoking and exercise among physical education teachers in Turkey. An online questionnaire was used to collect data. The responses of 1,995 teachers who completed the questionnaire were evaluated. The mean age of the participants was 31.0 +/- 4.7 years; 67.4% of the participants were male. The smoking rate was 65.2%. The mean age of onset of smoking was 16.6 +/- 2.6 years. The age of starting smoking increased with higher parental education level. There were no differences between smokers and nonsmokers with respect to gender. Of smokers, 51.2% were married; 52.4% were in the 30-39 year old age group. The most common reasons for starting smoking were the influence of friends and emulation. The most common reason for trying to quit smoking among men was future health concerns and among women was current health concerns. We found smoking was less common among participants who exercised regularly. The level of nicotine dependence was significantly lower among participants who exercised regularly compared to those who did not. This study suggests physical education teachers, who are role models for their students, have a high smoking rate. We believe urgent action is needed to reduce the smoking rate and increase the quit rate among physical education teachers.
Keywords: Adult; Age Factors; Cross-Sectional Studies; Exercise; Faculty; Female; Humans; Male; Peer Group; Physical Education and Training; Sex Factors; Smoking; Smoking Cessation; Socioeconomic Factors; Tobacco Use Disorder; Turkey; adult; age; article; cross-sectional study; exercise; female; human; male; peer group; physical education; psychological aspect; sex difference; smoking; smoking cessation; socioeconomics; statistics; tobacco dependence; Turkey (republic); university